The attitude of class nine and ten students towards solving mathematical word problems - Chimmi Dendup; Deepak Raj Chetri; G. Christymary Rani (USN Kolaka, 2022)
The study was conducted to understand the attitude towards solving mathematical word problems of 483 class nine and ten students. The quantitative method was used with purposive sampling, including all the students. Survey questionnaires with a fivepoint Likert scale were validated through pilot testing with 20 students and obtained a Cronbach’s alpha of 0.88. Views of students on attitude towards solving word problems, motivation of students, and implication of language in solving word problems were collected. MS Excel’s data analysis tool was used to analyze data using percentages, frequencies, descriptive analysis, and correlation. Two-sample t-test for the sample mean was used to see the significance of gender difference. The findings revealed a high positive attitude towards solving word problems. Students were motivated to solving word problems, the teacher is rated as the source of motivation. There was a high positive correlation between language and their love for solving mathematical word problems. There was no significant gender difference observed in attitude and motivation but gender difference was significant in the importance of language in solving word problems. Male students had a stronger belief than a female that language plays a vital role in one’s efficacy in solving mathematical word problems. Recommendations are suggested to the subject teachers to enable them to develop better instructions based on reflection.